Effect of bottom ash on the strength characteristics of fly ash and bottom ash mixtures - Ling, Jacky Jia Yii (2013)
One of the sources to produce electricity is coal. The major problem of the coal combustion based power plant is producing huge quantities of solid waste. Fly ash (FA) and bottom ash (BA) are two major contributions in the coal combustion products (CPP). Generally, most CPP are just dumped into the waste pond. The insufficient place for waste dumping is becoming an issue since the amount of CPP waste is increasing drastically. Recently, there are efforts to use the FA and BA together as mixtures in geotechnical engineering works. This paper focuses on the effect of BA content on the strength characteristic of fly ash and bottom ash mixtures, for coal ash taken from the Tanjung Bin power plant in Johor, Malaysia. This study investigates the effect of curing period on the morphology, chemical and strength characteristic of FA-BA mixtures that consists of 30 % and 70% BA.The mixtures had been tested in laboratory through Scanning Electron Microscopic test, X-Ray Fluorescences test and Consolidated Undrained triaxial test. Major chemical compostion of FA-BA mixtures are silica, alumina, ferum oxide and calcium oxide. The value of modulus of elasticity decreased with the increase of bottom ash content from 30% to 70% in the ash mixtures. The internal friction angle at critical state,??c’, was decreased as the content of BA is increased from 30% to 70%. Without curing periods, the increased of BA content from 30% to 70% did not give any significant effect on the critical state shear strength. However, after 28 days curing periods, the ?c’ was increased, but it is not that significant. It is also observed that the ?c’ of both mixtures with 30%BA and 70%BA are in the same range as the typical dense sands. Generally, it can be concluded that there is no significant effect on the shear strength properties at critical state for FA-BA mixtures at 30%BA and 70%BA. Hence, there will be a great potential to use a large quantity of BA in the mixtures without compromising the strength which can be a great benefit for usage in various geotechnical engineering works.